2021
DOI: 10.3390/ijms222111534
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Assessment of Long-Term Exposure to Non-Thermal Plasma Activated Water in Mice

Abstract: Non-thermal plasma activated water (PAW) has recently emerged as a powerful antimicrobial agent. Despite numerous potential bio-medical applications, studies concerning toxicity in live animals, especially after long-term exposure, are scarce. Our study aimed to assess the effects of long-term watering with PAW on the health of CD1 mice. PAW was prepared from distilled water with a GlidArc reactor according to a previously published protocol. The pH was 2.78. The mice received PAW (experimental group) or tap w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 97 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…The authors observed that there were not significant changes in the mineral composition and surface micro-morphology of the teeth. Moreover, the long-term exposure was not toxic to the tongue, oral mucosa, sublingual glands or other body organs, which presented normal structure and physiology [132]. In addition to not being harmful to mammalian cells, NTAPPs have been demonstrated to decrease inflammation and contribute to tissue repair [133].…”
Section: Anti-inflammatory Properties and Wound Healingmentioning
confidence: 99%
“…The authors observed that there were not significant changes in the mineral composition and surface micro-morphology of the teeth. Moreover, the long-term exposure was not toxic to the tongue, oral mucosa, sublingual glands or other body organs, which presented normal structure and physiology [132]. In addition to not being harmful to mammalian cells, NTAPPs have been demonstrated to decrease inflammation and contribute to tissue repair [133].…”
Section: Anti-inflammatory Properties and Wound Healingmentioning
confidence: 99%
“…PAS selectively kills colon, lung, cervical, bladder, melanoma, and breast cancer cells in vitro [ 76 , 77 , 78 , 79 , 80 ]. Preliminary studies on immuno-deficient nude mice by oral lavage treatment of CAP-activated water did not find lethal effects and acute toxicity [ 81 , 82 ]. Furthermore, the mice had no significant changes, including body weight, survival status, organ coefficient, function, and tissue structure of heart, liver, spleen, lung, and kidney [ 81 , 82 ].…”
Section: Cap-activated Solutions (Pas) and In Vivo Applicationmentioning
confidence: 99%
“…A recent study has shown the effects of long‐term (90 days) watering with PAW on the health of mice. [ 39 ] This is the only available study examining the intraoral administration of PAW. The authors conclude that the mice tolerated PAW very well, and PAW had no hematological, biochemical, or immunological effects in the blood and no histopathological effects on tissues throughout the body, including the colon.…”
Section: Resultsmentioning
confidence: 99%